Letters to the Editor - Tracey, Hugh (International Library of African Music, 1960)
From: Rev. B. Kingslake, Dr. The Rev. Brother Basil, Rev. A. M. Jones, Darius L. Thieme, Fr. Ch. v. Rÿthoven, J. H. Kwabena Nketia, Andrew Tracey.
Keywords: African Music